EXPLORING THE NEXUS BETWEEN MICRO SMALL MEDIUM ENTERPRISE, FINANCIAL INCLUSION, AND ECONOMIC GROWTH IN ASEAN 3 - Panji Tirta Nirwana Putra; Shanaiah Marie Amores; Ellizer ` Jan Ezack Cabahug (UNEJ e-Proceeding)
Small and medium enterprises (MSMe) are one of the major contributors of economic growth. The Philippines, Indonesia, and Thailand (later referred to as ASEAN 3) have identified this sector as the major component of the respective economy. However necessary to the sustainability, the lack of access to capital and credit necessary for the inception and sustainability of its operation(s) has proven to be a key complication. Financial inclusion is one of the solutions for small and medium-sized micro enterprises related to access to financial services. This paper analyzed the relationship of financial inclusion to the growth of micro, small and medium enterprises; and economic growth of the ASEAN 3. The authors have investigated financial inclusion using variable numbers of Automatic Teller Machine (ATM) per 100,000 people, commercial banks per 1,000 adults, and a number of bank branches. Panel vector auto regression (PVAR) were used in this study to investigate the relationship of financial inclusion and MSMe during Q12004 - Q42016. The results of the AR showed that the MSMe variable responded to the dynamics of financial inclusion, then the variable of economic growth also responded to the dynamics of MSMe in ASEAN 3.